KONSEPSI PEMBAGIAN KEKUASAAN NEGARA ISLAM KHILAFAH MENURUT HIZBUT TAHRIR DAN KEMUNGKINAN IMPLEMENTASINYA DI INDONESIA - Ahmadi Hasanudin Dardiri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2017)
The Islamic state idealized by Hizb ut-Tahrir has a system of government that is different from the existing system of government in the world today. The Islamic state has a different concept of power-sharing which is known in the growing doctrine of constitutional law. The concept of power sharing is similar to the concept of a state led by a king, since the caliph as head of state and head of government is given a very wide authority even including both judicial and legislative powers. This vast authority was given to the Caliph as an implementation of sovereignty in the hands of the Ummah who was then used to elect a caliph, so that the authority of the state derived from the Ummah was called by a caliph. The author analyzes the concept of the division of powers of Islamic countries according to Hizb ut-Tahrir to be applied in Indonesia which is a country with a majority of its population is Muslim. This analysis is based on the development of Indonesian constitutional phases since the founding of this country until today in order to find the possibility of conception to implementation of power sharing Khilafah Hizb ut-Tahrir Islamic state in Indonesia. This study suggests to Hizb ut-Tahrir for reconstruction and ijtihad new as